Portable flip keys / Husnie Shahriza Shari … [et al.] - Shari, Husnie Shahriza; Badioezaman, Nur Amirah Filzah; Wan Muhamad Saberi, Wan Halimaatun Nurulashikin; Mohd Nazri, Nor Adilla; Ahmad Nizar, Nurul Izzati (Research Innovation Business Unit, 2014)
Portable flip keys with its cover made of from plastic and some metal. It can be easily flipped to choose the correct key to be used. It is also convenient and saves space and we can avoid from miss placing all the keys. It can be customized such as choose the favourite colour for the cover. We can choose the design we want, small or big size. It can be made as key chain and looks neat and systematic in term of labelling the keys. It’s easy for us to find the right keys that we need. By using this product, we hope that people will be interested to buy and recommend our product to their family and friends.